Time Stamp Camera Application as A Presence to Improve the Quality of Education - Tri Widayatsih; Meilia Rosani; Nurlina Nurlina; Isnawijayani Isnawijayani; Diana Widhi Rachmawati (Jurnal Penelitian Pendidikan IPA, 2024)
The research was conducted at Yadika Lubuklinggau High School, Musirawas Regency, South Sumatra Province, aiming to determine the planning, organization, and implementation of supervision to improve quality. This research was conducted with a qualitative approach and used a case study methodology. The data collection technique is carried out by; observation, interviews, and documentation. The focus of the research is supervisory management to improve quality, with a sub-focus; on planning supervision, organizing supervision, and implementing supervision to improve the quality of Yadika Lubuklinggau High School, Musirawas Regency, South Sumatra Province. The research novelty is the time stamp camera application for attendance at Yadika Lubuklinggau High School. This research produces a supervision model at Yadika Lubuklinggau High School, where planning, organizing, and implementing supervision is carried out in predetermined stages and adds feedback from teachers as actors in the field so that the overall results provide an increase in the quality of Yadika Lubuklinggau High School as indicated by accreditation. A, student achievement at local, regional, and national levels.